Effect of balance training on falls in patients with osteoporosis: A systematic review and meta-analysis - Xin Zhou; Hui Deng; Xiaoping Shen; Qingliang Lei (Medical Journals Sweden, 2018)
Background: Balance training may be beneficial for patients with osteoporosis, although current results are inconclusive. The aim of this systematic review and meta-analysis was to explore the effect of balance training on falls in patients with osteoporosis. Methods: PubMed, Embase, Web of Science, EBSCO, and Cochrane Library databases were systematically searched. Randomized controlled trials (RCTs) assessing the effect of balance training vs usual activities on falls in patients with osteoporosis were included. Two investigators independently searched articles, extracted data, and assessed the quality of included studies. The primary outcome was fall frequency. This meta-analysis was performed using the fixed- or random-effect model when appropriate. Results: Six RCTs were included in the systematic review and 3 in the meta-analyses. Compared with control groups, a balance training intervention was found to significantly reduce the frequency of falls (risk ratio = 0.63; 95% confidence interval (95% CI) 0.42-0.95; p = 0.03) in patients with osteoporosis, but demonstrated no remarkable influence on the results of the Berg Balance Scale (mean difference -3.66; 95% CI -12.04-4.72; p = 0.39) and Timed Up and Go test (mean difference -1.79; 95% CI -6.05-2.47; p = 0.41). Conclusion: Balance training may significantly reduce the frequency of falls in patients with osteoporosis.